Current status of blood cockle (Tegillarca granosa) aquaculture off Myeik City, Myanmar - Yurimoto, Tatsuya; Aung-Aung-Aye; Cherry-Aung; Matsuoka, Kazumi; Koike, Kazuhiko (Journal of Fisheries, 2025)
Blood cockle aquaculture has played a vital role in the local economy around Myeik City, a major fishing hub in southern Myanmar, in recent years. This study aimed to assess the current state of aquaculture grounds and to contribute to the development of sustainable blood cockle farming. To determine the status of sowing aquaculture grounds, the main fishing sites were identified through boat-based surveys and interviews with local fishermen. Environmental characteristics of these areas were estimated using satellite imagery, along with weather and sea condition data. Additionally, shell length and whole weight of blood cockles purchased from a market in Myeik City were measured, and their digestive tube contents were examined. These results revealed that farming grounds were located around coves and creeks on small islands along the east coast of Kadan Island. These areas were characterised by high turbidity, with salinity remaining stable year-round at over 20 PSU. The annual chlorophyll-a concentration, approximately 4 μg L–1, indicated a consistent presence of phytoplankton, which was also confirmed by the digestive content analysis. However, compared to data on blood cockles from other regions reported in related studies, those collected after the rainy season were noticeably lighter in weight, indicating a leaner condition. These findings suggested that alternating the use of offshore and coastal aquaculture grounds according to the rainy and dry seasons may enhance farming efficiency and realise sustainable aquaculture practices.